Perlindungan Hukum Terhadap Tenaga Pendidik - Nurmala, Leni Dwi (Universitas Gorontalo, 2018)
One form of protection given to teachers in performing their professional duties is legal protection. This legal protection includes legal protection against acts of violence, threats, discriminatory treatment, intimidation or unfair treatment of learners, parents of learners, society, bureaucracy or other parties. One of the educational problems faced by schools in general is the violence of teachers towards students who still often occur in the school environment.